EXTRACTION OF PHENOLIC COMPOUNDS AS ANTIOXIDANTS FROM SOME PLANTS AND THEIR CYTOTOXIC ACTIVITY AGAINST BREAST CANCER CELL LINE - Omran, Rabab; Taee, Zahraa Mal; Jassani, Mohammed Jal; Hashim, Hayder O (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of the study was to study the antioxidants and cytotoxic activities of phenolic extracts of some plants against breast cancer and normal cell lines. Methods: Phenolics were extracted from different parts of some plants (15) such as seeds, fruits, leaves, and rhizomes using methanol: ethanol: HCl: Distilled water at a ratio 50:29:1:20 (v:v:v:v). The contents of phenolics and flavonoids were estimated using gallic acid and quercetin as standards, respectively. The antioxidant activity was determined by 2,2Ë‹-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) radical scavenging assay. Phenolic flavonoids were partially purified by adsorption chromatography using a silica gel column from selected plants and assayed their cytotoxic activity against breast cancer cell line Michigan Cancer Foundation-7 (MCF-7) and a normal cell line of non-tumorigenic fetal hepatic cell line (WRL-68). Results: The Cinnamomum zeylanicum extract had the highest phenolic and flavonoid contents were followed by Lawsonia inermis, Citrullus colocynthis, Syzygium aromaticum, Peganum nigrum, and Phoenix dactylifera. The antioxidant activity of Curcuma longa, P. dactylifera, C. colocynthis, Solanum melongena, and C. zeylanicum extracts had the highest ability to scavenge the free radicals. The acetone fraction of P. dactylifera and C. colocynthis extracts had the minimum inhibition dose that kills 50% of cells inhibitory concentration 50 values 156.91 Î¼g and 1055.06 Î¼g against MCF-7 and 372.86 Î¼g and 153.8 Î¼g against WRL-68, respectively. While the S. melongena extract had less effect on both cell lines. Conclusions: Phenolics as antioxidant substances had moderate or variable effectiveness on normal and cancer cell lines, and the highest concentrations were cancerous poison impact may be on normal cells over than cancer cells.